IDENTIFIKASI POLA CURAH HUJAN PADA KONDISI EL-NINO MELALUI CITRA MODIS DI PROVINSI JAWA TIMUR - , RIFAT DARAJAT ([Yogyakarta] : Universitas Gadjah Mada, 2014)
One of remote sensing image that can be used to estimate rainfall for regional scope is MODIS image. This research aims to identify the algorithm that can be extended the information of cloud top temperature (CTT) and cloud albedo (ALB) as contributing parameters for rainfall estimation, to compare the pattern of rainfall estimation during el-nino and normal condition, and to know the validation rate of rainfall estimation for rainfall data measured at the rain station. Method of this research is to extract the information of CTT and ALB from MODIS image and rainfall data from rain station to get an equation of multiple linear regression. CTT information was obtained from two kind of algorithms as comparison, the algorithm of CTT 1 (Coll, et al., 1997) and algorithm of CTT 2 (Sobrino, et al., 2008). Which result to equation representning equation A (CTT 1 and ALB) and equation B (CTT 2 and ALB). The result of this research signify thatâs existed 2 algorithms containing CTT and ALB information are possible being utilized as contributing parameter to estimate rainfall. The comparison of rainfall during el-nino condition show to lower in intensity and distribution pattern more uneven over the study area compared to the normal condition. The validation rate of rainfall estimation has a value of no more than 60 percent and has a pattern show the over-estimate value compared to the rainfall data measured at the rain station. The rainfall estimation from MODIS images extend the variation of accuracy, so it is needed other parameter for next research, such as cloud type, cloud altitude and wind direction.